Women's informed choice and satisfaction with immediate postpartum long-acting reversible contraception in Georgia - Carla L. DeSisto; Arden Handler; Sadia Haider; Rachel Caskey; Nadine Peacock; Melissa Kottke; Kristin Rankin (BMC, 2018)
Abstract Background Several state Medicaid agencies have recently started reimbursing for long-acting reversible contraception (LARC) placement immediately postpartum. Women's perspectives are critical for ensuring that this change increases access to LARC while empowering women to choose the method and timing of contraception that best meets their needs. We conducted a pilot study in Georgia, which recently changed its Medicaid reimbursement policy, to assess women's informed choice and satisfaction with immediate postpartum LARC. Methods We sampled all women with a live birth paid for by Georgia Medicaid during November 2015 through February 2017 who received an immediate postpartum LARC. We then used a one-to-one match to sample women who did not receive immediate postpartum LARC. Women were contacted via telephone for a 25-30 min interview regarding their knowledge, attitudes, and behaviors related to immediate postpartum LARC and their satisfaction with postpartum contraception. We calculated descriptive statistics and components of informed choice overall and by receipt of immediate postpartum LARC, using chi-square tests to calculate differences by group. Results We approached 470 women and completed interviews with 51; 25 (49%) received immediate postpartum LARC (24 implants, 1 intrauterine device). Two-thirds reported their provider discussed the option of receiving immediate postpartum LARC during prenatal care, with over 90% reporting they received all the information they needed to make a decision. Most women believed the ideal time to begin using birth control postpartum is in the hospital immediately after delivery, although this differed significantly by women's receipt of immediate postpartum LARC. Most women who received immediate postpartum LARC reported they are very or extremely happy with their device, although 40% also reported wanting their device removed at some point. Conclusions Women on Medicaid in Georgia report making informed choices regarding immediate postpartum LARC. Among those who received immediate postpartum LARC, women report high levels of satisfaction.